High‐Performance Low‐Platinum Electrode for Proton Exchange Membrane Fuel Cells: Pulse Electrodeposition of Pt on Pd/C Nanofiber Mat. Issue 5 (20th February 2017) - Hong, Shaojing; Hou, Ming; Zeng, Yachao; Shao, Zhigang; Yi, Baolian
Abstract: A novel electrode (E−P electrode) with a nanofiber structure and Pd/C@dendritic Pt catalysts is prepared by using electrospinning and pulse electrodeposition (PED) techniques. The maximum power density of the E−P electrode is 1.43‐fold larger than that of the conventional electrode at the same cathode Pt loadings of 0.1 mg cm −1 . Owing to the in situ deposition of dendritic Pt on the surface of Pd in the Pd/C nanofiber mat, almost all Pt catalysts are accessible for oxygen. The electronic tuning between Pd and Pt enhances the oxygen reduction reaction activity of Pt catalysts. The large Pt surface area of the E−P electrode mitigates the oxygen‐transport resistance in comparison with that of the conventional electrode. After the accelerated degradation test for 10000 cyclic voltammetry cycles, the maximum power density of the E−P electrode only decreases by 12 %. The long‐term stability of the E−P electrode is ascribed to the Pd/C@dendritic Pt catalysts and nanofiber structure. Abstract : High in fiber : An electrospun nanofiber electrode with Pd/C@dendritic Pt catalysts prepared by using electrospinning and pulse electrodeposition techniques obtains a peak power density of 0.682 W cm −2 at a low Pt loading of 0.1 mg cm −2 . The utilization of Pt catalysts in the electrode is improved, owing to the nanofiber structure and the in situ deposition of Pt on the surface of Pd. The interaction between Pd and Pt as well as the exposed [111] facet of dendritic Pt enhance the ORR activity of Pt.